Influence Blocking Maximization in Social Networks under the Competitive Linear Threshold Model - He, Xinran; Song, Guojie; Chen, Wei; Jiang, Qingye (In Proceedings of the 12th SIAM International Conference on Data Mining (SDM'2012), Anaheim, CA, U.S.A., April, 2012., 2012)
In many real-world situations, different and often opposite opinions, innovations, or products are competing with one another for their social inﬂuence in a networked society. In this paper, we study competitive inﬂuence propagation in social networks under the competitive linear threshold (CLT) model, an extension to the classic linear threshold model. Under the CLT model, we focus on the problem that one entity tries to block the inﬂuence propagation of its competing entity as much as possible by strategically selecting a number of seed nodes that could initiate its own inﬂuence propagation. We call this problem the inﬂuence blocking maximization (IBM) problem. We prove that the objective function of IBM in the CLT model is submodular, and thus a greedy algorithm couldachieve1−1/e approximation ratio. However, the greedy algorithm requires Monte-Carlo simulations of competitive inﬂuence propagation, which makes the algorithm not efﬁcient. We design an efﬁcient algorithm CLDAG, which utilizes the properties of the CLT model, to address this issue. We conduct extensive simulations of CLDAG, the greedy algorithm, and other baseline algorithms on real-world and synthetic datasets. Our results show that CLDAG is able to provide best accuracy in par with the greedy algorithm and often better than other algorithms, while it is two orders of magnitude faster than the greedy algorithm.